“Cuidados de enfermería en una puérpera post cesárea con diabetes mellitus tipo ii descompesada” - Ayala Pastuña, Alicia Marisol (2024)
The case study focused on a 34-year-old postpartum patient with a medical diagnosis of decompensated type II diabetes mellitus. This condition meant that their blood sugar levels were outside normal ranges, which could cause significant health complications. Additionally, the patient had undergone a cesarean section, which added an additional level of complexity to her medical situation. She had a complicated health condition that required specialized care and comprehensive health management during the postpartum period. The patient received nursing interventions that played a crucial role in her management. Continuous monitoring of blood glucose levels was implemented, allowing insulin doses to be adjusted according to the patient's needs to maintain optimal glycemic control. She also received personalized education about her diabetes, including insulin administration, the importance of a balanced diet, and consistent glucose monitoring to encourage self-care and informed decision making. Additionally, emotional and psychological support was provided, recognizing the emotional challenges the patient faced. These nursing interventions were effective and led to significant improvements in the patient. Blood glucose levels stabilized, resulting in more effective control of his diabetes. There was also an improvement in her emotional well-being, and the patient gained confidence in her ability to manage her health condition. The study concluded by emphasizing the importance of specialized and personalized nursing care in postpartum patients with complex medical conditions, such as decompensated type II diabetes mellitus, always oriented towards continuous improvement and the patient's well-being.